RANCANGAN ALAT BANTU AJAR KETERAMPILAN KEPERAWATAN DASAR PADA AKADEMI KEPERAWATAN TELANAI BHAKTI JAMBI - Lucy Simorangkir (JURNAL AKADEMIKA)
Nursing process is a series of follow up nursing to do foster care nurses systematically, planned, ongoing, and professional. Students also sometimes bored and hard to understand with educated manpower just explained without clear visualization and advertising. It therefore in this case required the support and tools simplify the submission of material to the students let alone currently most students already have a laptop/notebook. One of them is by building a stone tool learning multimedia-based learning process of Europass is more attractive, more interactive, the amount of teaching time may be reduced, the quality of student learning can be enhanced and the process of teaching and learning can take place where and at any time, as well as the learning attitude of students could be improved. For that final assignment will apply tools learning using macromedia flash 8.